THE EFFECT OF PHOSPHORUS-CONTAINING TECHNOGENIC WASTE ON HYDROBIONTS: Гидробионттар (Experimental biology, 2023)
The results of studies on the effect of phosphorus-containing waste on hydrobiont organisms are presented. When studying the effects of phosphorus-containing waste (sludge and slag) on hydrobionts, different systematic categories of hydrobionts were used as test objects: species of diatoms: Phaeodactilum tricornutum, Sinedra ulna, Navicula gracilis, Amphora ovalis, Pinnularia viridis, unicellular green algae: Scenedesmus guadricauda; Scenedesmus protuberans, Chlorococcum sp., Chlorella vulgaris, Cyanobacteria Oscillatoria limosa, protozoa: Amoeba proteus, Amoeba limax, Euglypha acanthophora, Paramecium aurelia, Paramecium caudatum, Paramecium putrinum, Paramecium omrelia, Paramecium multinucleus, Stylonychia mytilus, Vorticella convallaria, invertebrates: Colpoda steinii, Rotatoria, Calldina, Aeolosoma, Nematoda. The results of biotesting samples of phosphorus-containing waste showed that the toxic effect on planktonic and benthic organisms depends on the quantitative and qualitative parameters of phosphorus-containing waste. It was found that the 1.0 % concentration of phosphorus-containing slags and slurries turned out to be non-toxic, a further increase in the concentration of waste to 10.0% has an acutely toxic effect. At the same time, phosphorus-containing sludge turned out to be more toxic than slag. Indicator species were identified: Synedra ulna, Amphora ovalis, Rotatoria, Calldina sp., which are eliminated from the composition of hydrobiocenosis
Keywords: phosphorus-containing sludge, phosphorus-containing slag, acute toxicity, chronic toxicity, hydrobionts.